A functional TNFRSF5 polymorphism and risk of non-Hodgkin lymphoma, a pooled analysis - Nieters, Alexandra (2011)
Interaction between CD40 and its ligand, CD154, has a key function in immune regulation. Recent experimental data support a role of deregulated CD40 signalling in lymphomagenesis. Data from earlier studies that are part of this pooling study implicate a functional polymorphism (−1C>T, rs1883832) in the TNFRSF5 gene encoding CD40 in the etiology of follicular lymphoma. Here, the association of this variant with non-Hodgkin lymphoma (NHL) risk was replicated in a European multicenter study of 855 NHL cases and 1,206 controls. In the combined analysis of 2,617 cases and 3,605 controls, carrying the TT genotype was associated with an increased risk for all NHL (OR = 1.4; p for linear trend = 0.00009), diffuse large B-cell lymphoma (OR = 1.6; p for linear trend = 0.002) and follicular lymphoma (OR = 1.6; p for linear trend = 0.001). These data suggest a possible role of this functional polymorphism in lymphomas originating within the germinal center.